Groundwater contamination by organic pollutants analysis and remediation - Kaluarachchi, Jagath J. (Reston, Virginia American Society of Civil Engineers, 2001)
"Groundwater contamination by organic pollutants has become an important topic since the early 1980s due to detection of large-scale contamination events. Since that time, substantial research efforts have been focused on developing new and innovative technologies and management approaches to clean up organic-contaminated sites. With the development of new and effective technologies, current research efforts are now more focused on risk assessment and management at contaminated sites, and remediation in complex geological environments. Although research, technology transfer, and public education have been active links of the overall effort, still there is limited technology transfer and understanding of common remediation technologies and corresponding analysis among practitioners and managers. The goal of this monograph is to provide some insight into the remediation technologies associated with the saturated subsurface and corresponding analysis. It is intended to improve the understanding of both existing practitioners and beginning engineers, geologists, water chemists, and biologists."
Keywords: Organic water pollutants -- Analysis; Groundwater -- Pollution; Groundwater -- Purification; Electronic books